Wa7 Steqstum Ti Amha Swa7 (We Keep All The Goodness) ... - Coombs, Pascal; Fang, Stella; Patel, Ravi; John, Joanne; Min, Jason; Leung, Larry (Borealis, 2023)
A BC First Nation is taking a proactive approach to tackling youth crime through the development and implementation of restorative justice programming. To gain a better understanding of what other First Nations restorative justice programs look like and to provide recommendations on best practices for youth crime programs, the First Nation collaborated with students from the Entry-to-Practice PharmD Program at the University of British Columbia. Project team members worked with the Youth Crime Prevention Manager of the First Nation to create a literature review and recommendations for the development of the youth restorative justice program. A literature search was performed to review existing Indigenous youth-based restorative justice services and programs and recommendations from government publications in the development of Indigenous-focused social services and programs. Seventeen key articles discussed in the final report were summarized in a written report. A final report containing recommendations ...